ZNF667 attenuates leukocyte‐endothelial adhesion via downregulation of P‐selectin in skin flap following remote limb ischemic preconditioning. (18th March 2021) - Chen, Zhuang; Liu, Haifen; Li, Yuanbin; Zhou, Zhangfu; Qiu, Jizhe; Tang, Yi; Cui, Taotao
Abstract: We assessed the effects and potential mechanism of romote ischemic preconditioning (RIPC) on leukocytes‐endothelium cell adhesion in the flap microvessel after ischemia‐reperfusion (I/R) injury. Eight hours after reperfusion, edema and intravascular leukocyte aggregation were reduced and microvessels were more obvious in the group with superficial inferior epigastric artery (SIEA) perforator flap (SIEA‐flap) subjected to RIPC than in the I/R group. Zinc finger protein 667 (ZNF667) was significantly increased but P‐selectin was decreased in the flaps subjected to RIPC, compared to those in the I/R group. The low expression of P‐selectin was associated with ZNF667 expression and activation in human dermal microvascular endothelial cells in response to hypoxic preconditioning. ZNF667 bound to the P‐selectin promoter region, suppressing its transcription through a special core sequence. The ablation of P‐selectin by small interfering RNA effectively prevented the leukocytes‐endothelium cell adhesion effect of ZNF667‐knockdown. ZNF667 upregulation attenuates leukocyte‐endothelial cell adhesion by negatively regulating the expression of P‐selectin in SIEA‐flap subjected to RIPC.